Clinicopathologic characteristics of follicular lymphoma in hepatitis C virus‐infected patients. Issue 3 (1st April 2020) - Hosry, Jeff; Miranda, Roberto N.; Samaniego, Felipe; Angelidakis, Georgios; Torres, Harrys A.
Abstract: Follicular lymphoma (FL) is the most common subtype of indolent non‐Hodgkin lymphoma. It has been hypothesized that chronic hepatitis C virus (HCV) infection stimulates IGH‐BCL2 clone proliferation, leading to development of FL. Furthermore, regression of FL after antiviral treatment without chemotherapy has been reported in HCV‐infected patients. To clarify the relationship between HCV and FL, we compared the prevalence of IGH‐BCL2 translocation and other clinicopathologic characteristics between HCV‐infected and HCV‐uninfected FL patients and determined the impact of HCV eradication on the oncologic outcomes of HCV‐infected FL patients. The study included HCV‐infected patients (cases) with FL seen at our institution during 2004‐2018. Cases were matched with HCV‐uninfected FL patients (controls) according to year of lymphoma diagnosis, sex, and hepatitis B serology. We studied 19 cases and 57 controls. More cases than controls had splenic involvement of FL (26% vs 5%, P = 0.02), higher histologic grade (grade 3 in 56% vs 24%, P = 0.01), absent or weak CD10 expression (42% vs 11%, P = 0.005), and absent BCL2 expression (33% vs 4%, P = 0.004). Compared to controls, cases had a lower rate of detection of IGH‐BCL2 translocation (31% vs 68%, P = 0.02). Finally, cases with a sustained virologic response (virologic cure of HCV) had a better 10‐year overall survival rate than did cases not treated with antivirals or controls ( P = 0.001). In conclusion, HCV‐infected patients with FL have unique clinicopathologic characteristics including improved overall survival with HCV eradication. The pathogenesis of FL in HCV‐infected patients seems unrelated to antiapoptotic effect of IGH‐BCL2 rearrangement.